'I'm always up against a brick wall with them': parents' experiences of accessing support for their child with a newly recognised developmental disorder. (1st March 2022) - McCarthy, Robyn; Blackburn, Carolyn; Mukherjee, Raja; Fleming, Kate; Allely, Clare; Kirby, Lauren; Cook, Penny A.
Abstract : Three of the most prevalent developmental disorders (DDs) are autism spectrum disorder (ASD), attention‐deficit/hyperactivity disorder (ADHD) and fetal alcohol spectrum disorder (FASD). As part of a study screening for DDs in Greater Manchester, UK, a unique opportunity was taken to explore parents' experiences of receiving reports about their child's previously unrecognised DD. Six parents out of a possible 16 took part in interviews, which were analysed thematically. Findings drawn from parental responses revealed a number of barriers to accessing support for their child's additional needs, including perceived resistance from schools, particularly for quiet, well‐behaved girls, and difficulty in accessing assessment or referrals. There needs to be greater awareness of additional needs in children without externalising behaviours, the presence of gender‐specific differences in the presentation of DDs, and FASD as a commonly occurring DD. Ultimately, better support for children with DDs would reduce the burden of unmet needs for the children and their families, and for wider services.